Force and Boldness: Cumulative Assets of a Successful Crayfish Invader - Pârvulescu, Lucian; Stoia, Dan Ioan; Miok, Kristian; Ion, Mihaela Constanţa; Puha, Adela Estera; Sterie, Melania; Vereş, Mihajel; Marcu, Ioan; Muntean, Mirela Danina; Aburel, Oana Maria (Frontiers in Ecology and Evolution, 2021)
Multiple causes can determine the disturbance of natural equilibrium in a population of a species, with a common one being the presence of invasive competitors. Invasives can drive native species to the resettlement of the trophic position, changing reproduction strategies or even daily normal behaviours. Here, we investigated the hypothesis that more effective anatomical features of an intruder (Faxonius limosus) come with increased boldness behaviour, contributing to their invasion success in competition against the native species (Pontastacus leptodactylus). We tested the boldness of specimens representing the two species by video-based assessment of crayfish individuals’ attempts to leave their settlement microenvironment. The experiment was followed by a series of measurements concerning chelae biometry, force and muscle energetics. The native species was less expressive in terms of boldness even if it had larger chelae and better muscular tissue performance. In contrast, because of better biomechanical construction of the chelae, the invasive species was capable of twice superior force achievements, which expectedly explained its bolder behaviour. These findings suggest that, in interspecific agonistic interactions, the behaviour strategy of the invasive crayfish species is based on sheer physical superiority, whereas the native crayfish relies on intimidation display.